Étude de la faune ophidienne de l'Égypte ancienne - Brix, Nicole Pierrette (Books on Demand)
The present study tries to reconstruct the ophidian fauna of ancient Egypt and to emphasize, by means of iconographic and written documents, the knowledges Egyptian people had about snakes living in their country. The first part studies the generalities concerning snakes ; the second part contains monographs treating the different ophidian species that occuped an important place in Egyptian religion and daily life